A Rare Cause of Seizures: Hypomagnesemia Type 1 - Inês Gameiro; Catarina Pinto Silva; Marta Machado; Carolina Cordinhã; Carmen do Carmo; Clara Gomes (Publicações Ciência e Vida, 2023)
Hypomagnesemia type I is a rare autosomal recessive disorder characterized by severe hypomagnesemia, often accompanied by hypocalcemia. This disease is caused by mutations in the TRPM6 gene (which encodes the respective channel), leading to reduced intestinal absorption of magnesium and increased renal excretion due to a defect in reabsorption in the distal convoluted tubule. It usually manifests itself in the first months of life, with symptoms of neuromuscular hyperexcitability and seizures, refractory to antiepileptic therapy. Treatment consists of administering high doses of magnesium throughout life. Here, we report a case of hypomagnesemia type I with a novel pathogenic variant of TRPM6 in a 5-month-old girl who developed refractory seizures due to hypomagnesemia.